Analisis Harga Pokok Produksi dan Harga Pokok Penjualan pada Ken Jus and Drink Berbasis Metode Full Costing - Putri, Amelia; Sari, Anggun Indah; Rahmah, Fatya; Fadia, Hana’; Lestari, Tri (CV Warnak Johanna Nusantara, 2025)
This article aims to analyze the impact of calculating Production Costs (HPP) and Sales Costs (HPPj) on profit from sales made by Ken Jus and Drink UMKM by applying the full costing method. Many UMKM actors still face difficulties in setting the right selling price due to a lack of comprehensive understanding of production costs. The full costing method is applied in this study to find all cost components, both direct and indirect, that play a role in the production process. This study uses a descriptive quantitative approach by collecting data through direct interviews with business owners and journals as references. The findings of this study indicate that the use of the full costing method provides a clearer picture of the cost structure and can be used as a more accurate basis for determining selling prices and measuring profits from sales. Thus, this method plays a role in making more efficient financial decisions for UMKM.